Analyses of Self – Administration Reality of Central Sport Federation Presidents from Administrative Bureau Point of View in Iraq - Abdul Hussein, Atheer Ailan; Khadem, Abdul Rezaq (Journal of Physical Education, 2021)
The importance of the research lies in self – administration being a modern topic in sport administration in general and in Iraqi central sport federation’s administration in particular.  Self - administration positively affect high self–esteem in members of the administrative board in Iraqi central sport federations. It also contributes to future vision and strategy planning for each federation to achieve winning in competitions.